Efficiency in employee-owned enterprises: An econometric case study of Mondragon - Saioa Arando; Monica Gago; Derek C. Jones; Takao Kato (Institute for the Study of Labor (IZA), 2011)
We provide the first econometric study of efficiency for a member of the Mondragon group of worker cooperatives. Eroski is a retail distribution chain and, most unusually, there are two distinct types of hypermarkets: (i) cooperatives with significant employee ownership and voice; and (ii) GESPAs with modest employee ownership and limited voice. For supermarkets the chain includes conventional firms with no employee ownership as well. Our key data are a panel of monthly observations from February 2006 through May 2008, a total of 9,800 observations for supermarkets and 2,150 for hypermarkets. By estimating first difference models we find that hypermarket stores with cooperative ownership grow sales significantly faster than GESPA stores. For supermarkets overall we find no significant difference in performance among the three types of stores. However, for a particular segment of the supermarket called SUPERMARKET CITY (a subgroup of small supermarkets for which having better customer service employees is particularly important), cooperatives are found to outperform conventional stores. To investigate mechanisms that help explain why cooperatives are better performers we provide additional evidence that takes account of the role of the more extensive opportunities for employee involvement and training, and stronger economic incentives that exist in cooperatives. Finally, while cooperative members are better paid than their peers in comparable firms, individual-level data also show that job satisfaction is actually lower for workers in cooperatives than for GESPA workers. Though this may be a simple reflection of high worker expectation in cooperatives, cooperatives may well be indeed a high-stress work system. The overall assessment of cooperatives will need to be nuanced.
urn:nbn:de:101:1-201105306363
Keywords: J54; D21; 330; employee ownership; producer cooperatives; labor managed firm; productive efficiency; Mondragon; shared capitalism